Autonomic nervous system and primary open angle glaucoma – pathogenetic and clinical correlations - Wierzbowska, Joanna; Wierzbowski, Robert; Stankiewicz, Andrzej; Robaszkiewicz, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Primary open angle glaucoma is linked to autonomic nervous system dysfunction. In a review the role of autonomic nervous system as an important determinant of systemic hemodynamic parameters such as heart rate and blood pressure, was presented. Human circadian clock and its impact on autonomic nervous system was emphasized. Finally some autonomic function tests and therapeutical implications were described.